Prediction of the Pantograph/Catenary Wear Using Nonlinear Multibody System Dynamic Algorithms - Siripong Daocharoenporn; Mongkol Mongkolwongrojn; Shubhankar Kulkarni; Ahmed A. Shabana (My University, 2019)
In this investigation, computational multibody system (MBS) algorithms are used to develop detailed railroad vehicle models for the prediction of the wear resulting from the pantograph/catenary dynamic interaction. The wear is predicted using MBS algorithms for different motion scenarios that include constant-speed curve negotiation and acceleration and deceleration on a tangent (straight) track. The effect of the vehicle vibration in these different motion scenarios on the contact force is further used to study the wear rates of the contact wire. The wear model used in this investigation accounts for the electrical and the mechanical effects. The nonlinear finite element (FE) absolute nodal coordinate formulation (ANCF), which is suitable for implementation in MBS algorithms, is used to model the flexible catenary system, thereby eliminating the need for using incremental-rotation procedures and co-simulation techniques. In order to obtain efficient solutions, both the overhead contact line and the messenger wire are modeled using the gradient-deficient ANCF cable element. The pantograph/catenary elastic contact formulation employed in this study allows for separation between the pantograph panhead and the contact wire, and accounts for the effect of friction due to the sliding between the pantograph panhead and the catenary cable. The approach proposed in this investigation can be used to evaluate the electrical contact resistance, contribution of the arcing resulting from the panhead/catenary separation, mechanical and electrical wear contributions, and the effect of the pantograph mechanism uplift force on the wear rate. Numerical results are presented and analyzed to examine the wear rates for different motion scenarios.
Keywords: Pantograph; Catenary; Contact force; Multibody system; Electrical Contact Performance and Analysis